Development of an IgY Antibody-Based Immunoassay for the Screening of the CYP2E1 Inhibitor/Enhancer from Herbal Medicines - Jiang, Zhihui; Jiang, Xuemei; Li, Cui; Xue, Huiting; Zhang, Xiaoying (Frontiers in Pharmacology, 2016)
Abstract Cytochrome P450 (CYP) 2E1 is an important enzyme involved in the metabolism of many endogenous and exogenous compounds. It is essential to evaluate the expression of CYP2E1 in the studies of drug-drug interactions and the screening of drugs, natural products, and foodstuffs. The present work is a feasibility study on the development of immunoassays using a specific and sensitive chicken-sourced anti-CYP2E1 IgY antibody. Cloning, expression, and purification of a recombinant CYP2E1 (mice origin) protein were carried out. Anti-CYP2E1 IgY antibodies were generated by immunizing white Leghorn chickens with purified recombinant CYP2E1 protein and were purified by immune affinity chromatography. The IgY titer attained a peak level (≥1:128,000) after the 5th booster injection. For evaluation of the expression of CYP2E1 in different herbal treatment samples, the mice were treated by oral gavage for 3 days with alcohol (50% 15 mL/kg), acetaminophen (APAP, 300 mg/kg), Cornus officinalis extract (100 mg/kg), Alhagi-honey extract (100 mg/kg), Apocynum venetum extract (100 mg/kg), hyperoside (50 mg/kg), isoquercetin (50 mg/kg), 4-hydroxyphenylacetic acid (50 mg/kg), 3-hydroxyphenylacetic acid (50 mg/kg), and 3,4-hydroxyphenylacetic acid (50 mg/kg). The expression of CYP2E1 was determined by western blot analysis, immunohistochemistry, ELISA, and immunomagnetic beads using anti-CYP2E1 IgY in liver tissue. The results showed that Cornus officinalis extract, Alhagi-honey extract, Apocynum venetum extract, hyperoside, isoquercetin, and their xenobiotics 4-hydroxyphenylacetic acid, 3-hydroxyphenylacetic acid, and 3,4-hydroxyphenylacetic acid significantly decreased CYP2E1 levels. Alcohol and APAP treatments significantly increased CYP2E1 levels as analyzed with western blot analysis, immunohistochemistry, and ELISA. The immunomagnetic bead method is suitable for large-scale screening, and it is a rapid screening (20 min) that uses a portable magnet and has no professional requirements for the operator, which makes it useful for on-the-spot analysis. Considering these results, the anti-CYP2E1 IgY could be applied as a novel research tool in screening for the CYP2E1 inhibitor/enhancer.